PELANGGARAN KESANTUNAN BERBAHASA DALAM DIALOG UJIAN SKRIPSI DI STKIP PGRI BANDAR LAMPUNG - ., Supriyono (Lentera: Jurnal Ilmiah Kependidikan, 2014)
The aim of this research is to describe, discover, and explain the language politeness in paper examination dialogue at STKIP PGRI Bandar Lampung. Principal problems in this research is to know how the violation at language politeness in the dialogue of paper examination at STKIP PGRI Bandar Lampung. This research used a qualitative approach by using content analysis methods and inductive procedures. The data collecting by recording conversations, noted conversation; classify conversations, and select conversation units from research corpus as a analyzed data unit. The result of researh showed in the dialogue paper examinantion at STKIP PGRI Bandar Lampung between examiner and students have found the violation of language politeness. The results of research recommended for consideration in preparing the teaching programe pragmatics subjects, discourse analysis, and speaking skills; and for more advanced research based on the speaker background of the other experts.